Business Modeling and Software Design Second International Symposium, BMSD 2012, Geneva, Switzerland, July 4-6, 2012, Revised Selected Papers - Shishkov, Boris (Lecture Notes in Business Information Processing, 2013)
This book contains the extended and revised versions papers from the Second International Symposium on Business Modeling and Software Design (BMSD 2012), held in Geneva, Switzerland, in July 2012, organized and sponsored by the Interdisciplinary Institute for Collaboration and Research on Enterprise Systems and Technology (IICREST), in cooperation with the Center for Telematics and Information Technology (CTIT), the Institute for Systems and Technologies of Information, Control and Communication (INSTICC), and Technical University of Sofia. The theme of BMSD 2012 was "From Business Modeling to Service-Oriented Solutions". The 7 papers presented in this book were carefully reviewed and selected from 46 submissions. Each paper was reviewed by at least two internationally known experts from the BMSD Program Committee. The papers focus on business models, service engineering, and information systems architectures.